The Issue of Noncompliance in Attention Check Questions: False Positives in Instructed Response Items. Issue 4 (November 2022) - Silber, Henning; Roßmann, Joss; Gummer, Tobias
Attention checks detect inattentiveness by instructing respondents to perform a specific task. However, while respondents may correctly process the task, they may choose to not comply with the instructions. We investigated the issue of noncompliance in attention checks in two web surveys. In Study 1, we measured respondents' attitudes toward attention checks and their self-reported compliance. In Study 2, we experimentally varied the reasons given to respondents for conducting the attention check. Our results showed that while most respondents understand why attention checks are conducted, a nonnegligible proportion of respondents evaluated them as controlling or annoying. Most respondents passed the attention check; however, among those who failed the test, 61% seem to have failed the task deliberately. These findings reinforce that noncompliance is a serious concern with attention check instruments. The results of our experiment showed that more respondents passed the attention check if a comprehensible reason was given.